2014
DOI: 10.1118/1.4897382
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal filtering of MR‐temperature artifacts arising from bowel motion during transurethral MR‐HIFU

Abstract: Purpose: Transurethral MR-HIFU is a minimally invasive image-guided treatment for localized prostate cancer that enables precise targeting of tissue within the gland. The treatment is performed within a clinical MRI to obtain real-time MR thermometry used as an active feedback to control the spatial heating pattern in the prostate and to monitor for potential damage to surrounding tissues. This requires that the MR thermometry measurements are an accurate representation of the true tissue temperature. The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Second, movement of tissue interfaces leads to changes in the main magnetic (B 0 ) field of the scanner, invalidating some underlying assumptions of the reconstruction algorithm. For slow changes in the B 0 field, techniques are under development to filter artefacts [104,105] or use a silicon [106] or fat [107] reference, but fast changes require dedicated motion-robust approaches. Finally, there are motion artefacts from convective currents or externally recirculated fluids inside the bladder that induce image distortion and temperature rise calculation errors.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Second, movement of tissue interfaces leads to changes in the main magnetic (B 0 ) field of the scanner, invalidating some underlying assumptions of the reconstruction algorithm. For slow changes in the B 0 field, techniques are under development to filter artefacts [104,105] or use a silicon [106] or fat [107] reference, but fast changes require dedicated motion-robust approaches. Finally, there are motion artefacts from convective currents or externally recirculated fluids inside the bladder that induce image distortion and temperature rise calculation errors.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…A study was recently conducted by Schmitt et al 29 in which temperature and thermal dose measurements were corrected with respect to susceptibility artifacts arising from bowel motion during MRg-HIFU interventions in the prostate. While in the current work we propose a correction strategy based on displacements provided by a motion estimation algorithm, their study focuses on developing and implementing a filter that excludes temperature information in regions that manifest a higher temperature fluctuation than the heated area.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of successful implementation of transurethral CBUS ablation of prostate with multi-planar PRFS-based MRTI are reported in the literature [36, 46-48, 50, 52-55, 81, 82]. Ancillary studies related to diffusion-weighted imaging [80] and refinement of MR techniques for motion compensation have also resulted from similar work [76, 113, 114]. MR thermometry techniques have also been explored for monitoring endoscopic ablation of liver and pancreatic tumors [58, 65, 66].…”
Section: Image Guidancementioning
confidence: 99%
“…Recent investigations described above have demonstrated that the artifacts generated from the devices themselves can be minimized with proper selection of MR compatible materials and fabrication techniques, so that regions as close as 1-3 mm from the applicator extending to the outer treatment boundary can be effectively monitored [49, 55, 82]. Tissue motion related errors can be compensated through multi-baseline or multi-reference imaging [76, 115-117]. Background or baseline phase drift errors can be compensated by tracking phase changes outside the heated region [115].…”
Section: Image Guidancementioning
confidence: 99%
See 1 more Smart Citation